Dissociative ionization of N2 by fast electron impact: roles of molecular orbitals. (29th September 2017) - Zhang, Y; Wang, X; Zhu, L F; Lu, D; Hutton, R; Zou, Y; Wei, B
Abstract: Dissociative single, double and triple ionization of N2 induced by fast electron impact are studied using the cold target recoil-ion momentum spectroscopy technique. Kinetic energy releases (KERs) are determined and possible states of parent ions are analyzed for the dissociation channels ( N 2 + → N + + N, N 2 2 + → N 2 + + N ) and also Coulomb explosion channels ( N 2 2 + → N + + N +, N 2 3 + → N 2 + + N + ) . As the electron-impact energy increases, the different dissociation channels behave quite differently. For example, the KER spectra of the channel N 2 + → N + + N show that the intensity of the low-KER part increases and that of the high-KER part decrease, while the KER spectra of the channel N 2 2 + → N + + N + seem to remain unchanged. Comparing and analyzing the KER distributions (KERDs) of the different dissociation channels, we find that both single and double ionization from different molecular orbitals, i.e. outer or inner valence orbitals can give rise to different decay channels with different electron energy dependence. Therefore, from the perspective of KERD, the present work clearly reveals the important roles of different molecular orbital ionization in the dissociation of molecule.